Heat Shock Proteins, L-Arginine, and Asymmetric Dimethylarginine Levels in Patients With Obstructive Sleep Apnea Syndrome - In, Erdal; Ozdemir, Cengiz; Kaman, Dilara; Sokucu, Sinem Nedime (Elsevier Espana Slu, 2015)
Objective: Vascular endothelial inflammation and enhanced oxidative stress are important factors in the pathogenesis of obstructive sleep apnea syndrome (OSAS). The aim of this study was to determine the levels of heat shock protein (HSP) 27, HSP70, HSP90, L-arginine, and asymmetric dimethylarginine (ADMA) in patients with OSAS and determine their relationship with cardiovascular (CV) risk factors. Material and methods: Forty patients with OSAS, comprising 26 with and 14 without traditional CV risk factors (obesity, hypercholesterolemia, diabetes, hypertension, and smoking), and 20 control subjects without OSAS were included. All patients underwent a full polysomnographic evaluation, and blood samples were obtained in the morning after the night the diagnostic study was performed. Results: No significant differences were found in serum HSP27 and HSP70 levels between the groups. HSP90 and ADMA levels increased significantly, whereas L-arginine levels decreased significantly in patients with OSAS, both with and without CV risk factors, compared with controls, but were not different among the subgroups. In all patients with OSAS, serum HSP70 levels were positively correlated with a percent time with saturation <90% (r=.349, P=.027). Serum L-arginine levels were negatively correlated with desaturation number (r=-.360, P=.022) and apnea-hypopnea index (r=-.354, P=.025) and positively correlated with mean oxygen saturation (r=.328, P=.039). Conclusion: Serum levels of HSP90 and ADMA increased, whereas those of L-arginine decreased in patients with OSAS regardless of CV risk factors. These findings indicate the presence of oxidative stress and endothelial dysfunction in patients with OSAS. (C) 2014 SEPAR. Published by Elsevier Espana, S.L.U. All rights reserved.
Concentraciones de proteínas de estrés térmico, L-arginina y dimetilarginina asimétrica en pacientes con síndrome de apnea obstructiva del sueño
Keywords: Obstructive sleep apnea syndrome; Heat shock proteins; Asymmetric dimethylarginine; L-arginine; Endothelial dysfunction; Oxidative stress